Respuesta :

9514 1404 393

Answer:

  3

Step-by-step explanation:

The radicals get in the way a bit, so we can define ...

  x = √p

  y = √q

Then the equation is ...

  (x +y)/(1-x) = (4x+y)/(1-x^2)

Multiplying by (1-x^2), we have ...

  (x +y)(1 +x) = 4x +y . . . . . . using 1-x^2 = (1-x)(1+x) the 1-x factor cancels

  x^2 +xy +x +y = 4x +y . . . eliminate parentheses

  x(x +y) = 3x . . . . . . . subtract (x+y)

  x +y = 3 . . . . . . . . . . divide by x

This is the sum we're looking for:

  √p +√q = 3

uhidk7

Answer: The answer is 3

Step-by-step explanation: